CD INDEX, A NEW METHODS FOR MEASURE BANKING CRISIS - Amir Ambyah Zakaria; Musdholifah . (Journal of Management and Business, 2016)
The global financial crisis has a bad impact for domestic financial systems. Banking system is important component from financials system which has more attention. Evidence from Indonesia crisis in 1998 from Asian currency crises, subprime mortgage America in 2008,  the Volatility of US Economic in 2011, and slowdown china economic in 2015 that made systematic risk for financial systems and banking system in Indonesia. Crisis identification for individual bank is important to avoid systematic risk. Using Index for measuring banking crisis will give crisis signal before the crisis happen. Crisis and Default Index can predict and measure banking crisis more accurate than other measurement. The four components of banking risk crisis have been included. These components are liquidity risk, Credit risk, interest rate risk, and exchange rate risk. Furthermore, CD Index can describe duration of the crisis, periods of the crisis, and the component which can trigger a crisis. Samples of this research are all commercial banks that listed in Indonesian stock exchange period 2010-2014. The result is 18 banks which join Indonesian stock exchange have indicated crisis in 2011 and 2014. In 2010 BTN was identified Crisis, it caused the score of credit risk and investment risk is riskier than the others. Danamon bank has a bad score from credit component, it can trigger crisis in 2011. Then in 2012 and 2013 Sinarmas bank and J trust bank have been declared crisis. J trust bank was still in crisis in 2014, because it had a bad score for the all components.